2016
DOI: 10.3109/0886022x.2016.1163154
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of theophylline in preventing cisplatin-related nephrotoxicity in patients with cancer

Abstract: Objective: Cisplatin is a potent antineoplastic agent used and its major limiting side effect is nephrotoxicity. The aims of the study are early detection of acute kidney injury (AKI) with biomarkers and investigation of the potential nephron-protective effects of theophylline. Methods: Glomerular filtration rates (GFR), neutrophil gelatinase-associated lipocalin (NGAL), cystatin C were measured at 5th day of treatment in all of the patients. In addition, these parameters were measured repeatedly after the adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Several potential treatments of both Cis‐ and Ifos‐mediated AKI have been shown to mitigate renal tissue damage . A few human studies suggest that ameliorating chemotherapy‐associated AKI with medication is possible . Early and specific AKI markers will enhance future trials of Cis‐ and Ifos‐nephrotoxicity prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Several potential treatments of both Cis‐ and Ifos‐mediated AKI have been shown to mitigate renal tissue damage . A few human studies suggest that ameliorating chemotherapy‐associated AKI with medication is possible . Early and specific AKI markers will enhance future trials of Cis‐ and Ifos‐nephrotoxicity prevention.…”
Section: Discussionmentioning
confidence: 99%
“…A study of patients ( n = 33) revealed an AUC-ROC value for NGAL of 0.87 at 12 and 24 h. 21 Other studies have also revealed similar findings with an AUC-ROC value of 0.80 at 24 h signifying important predictive value for NGAL to reflect AKI. 56 Recent data also suggest that elevations in urinary NGAL may even be able to detect AKI as early as 2 h. 59 Interestingly, patients with a slow recovery from AKI had earlier and higher increases in urinary NGAL levels. 57 The time points selected for NGAL quantification are important.…”
Section: Neutrophil Gelatinase-associated Lipocalinmentioning
confidence: 99%
“…In our study, the addition of sildenafil plus theophylline with or without roflumilast combined with carboplatin or cisplatin showed increased apoptosis when compared with platinum-based drugs alone. Despite the high pharmacological doses 71 and questionable protective effect against cisplatin nephrotoxicity 72 , theophylline has been proposed as a potential anti-cancer drug combined with chemotherapeutic regimens for more than a decade. 36 , 43 , 73 , 74 Specifically, the synergistic effect of theophylline with chemotherapeutic drugs comes from the induction of apoptosis and the interference with the cell cycle.…”
Section: Discussionmentioning
confidence: 99%